Incisal Trait Variations Between Javanese and Chinese-Indonesians in Surabaya - Avianto, Rahmat; Alaydrus, Sayf Muhammad; Artaria, Myrtati Dyah; Chen, Yao-Fong (UI Scholars Hub, 2024)
Human teeth are unique since one population’s dental pattern might differ from another. Such specific dental characteristics, such as the incisor, are observable in each dentition. Objective: his study analyzed the population differences in Javanese and Chinese-Indonesian populations through observations of the incisal traits, namely winging, shoveling, and double shoveling. Methods: 50 dental casts (76 Javanese samples and 74 Chinese- Indonesian samples) were obtained from Dr. Myrtati Dyah Artaria’s private collection, stored in the Faculty of Medicine, Universitas Airlangga. The traits were observed and scored using the Arizona State University Dental Anthropology System (ASUDAS) and analyzed statistically using crosstab and chi-square methods. Results: Only three out of 13 test results exhibit significant differences (p < 0.05). Conclusion: The dentitions observed in the Chinese-Indonesian samples mirror the immense Chinese acculturation into Javanese cultures through interbreeding that happened generations ago. The gene flow between these two populations appears phenotypically in the dentitions, leading the Chinese-Indonesian samples in this study to express Sundadont traits despite their noticeable facial traits and heritage.